LaMnO3 Perovskite Activation of Peroxymonosulfate for Catalytic Palm Oil Mill Secondary Effluent Degradation - Panca Setia Utama; Wahyu Bambang Widayatno; Muhammad Rizwan Azhar; Hussein Rasool Abid; Wenchao Peng; Oki Muraza; Edy Saputra (Journal of Applied Materials and Technology, 2020)
The LaMnO3 perovskite catalyst was successfully synthesized using a simple solid-state reaction method. This catalyst is used to activate PMS in the organic content's degradation process in the secondary effluent palm oil mill (POMSE). The organic content in POMSE is equivalent to the COD value; thus the COD value is used as a parameter for the process's success. The catalyst performance test shows that the catalyst effectively reduces COD, and the waste meets the maximum threshold allowed by government regulations. The variables that affect the catalyst's effectiveness were the calcination temperature of the catalyst, catalyst loading, PMS concentration, and temperature. The temperature of calcination affects the perovskite crystal formation; the higher the temperature, the more active catalyst obtained. The catalyst loading and PMS concentration variables affect the degradation process of organic levels in POMSE; at low levels, the higher the catalyst loading and PMS concentrations will increase the effectiveness of the degradation process, but at certain levels, the addition of catalysts and PMS reduces the effectiveness of the process. LaMnO3-800oC catalyst presents the highest activity of 92.7% and met the allowable threshold of COD < 300 mg/L. The sequence for removal of COD among the three catalysts with an order of LaMnO3-800oC > LaMnO3-700oC > LaMnO3-600 oC. The pseudo-second-order kinetics equation fits the experimental data. The effect of temperature on the kinetics constant follows the Arrhenius equation. Furthermore, the catalyst obtained was stable, with no significant decrease in catalysts activity up to three runs.